2017
DOI: 10.1097/jsm.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Concussion in Ice Hockey—A Cohort Study Across 29 Seasons

Abstract: This study showed a significant increase of concussion IR and a trend toward longer rehabilitation periods due to concussion. Possible risk factors were discussed. Risk behavior and rehabilitation protocols should be prioritized areas in the research of concussion in ice hockey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…In retired NFL American football players, studies 23,24 have demonstrated a correlation between previous history of concussion and an increased incidence of lower extremity musculoskeletal injury including osteoarthritis. Cohort studies have demonstrated an increased risk of subsequent musculoskeletal injury following a concussive injury in professional sports including rugby union, 25 ice hockey, 26 Australian Rules Football 27 and soccer, 28 alongside a similar trend in US collegiate athletes 29,30 . A recent study 31 has also examined this relationship in adolescent high‐school athletes across various sports.…”
Section: Discussionmentioning
confidence: 99%
“…In retired NFL American football players, studies 23,24 have demonstrated a correlation between previous history of concussion and an increased incidence of lower extremity musculoskeletal injury including osteoarthritis. Cohort studies have demonstrated an increased risk of subsequent musculoskeletal injury following a concussive injury in professional sports including rugby union, 25 ice hockey, 26 Australian Rules Football 27 and soccer, 28 alongside a similar trend in US collegiate athletes 29,30 . A recent study 31 has also examined this relationship in adolescent high‐school athletes across various sports.…”
Section: Discussionmentioning
confidence: 99%
“…In general, participants dreamed about becoming better, finding worthwhile activities, becoming able to work full-time and being independent: "I've come to realise that I will live a life with troubles for the rest of my life. It's been 3…”
Section: ] People Generally Don't Really Understand; They See [A Concussion] As a Blow [ ] But I've Really Felt That It's Interfered Wimentioning
confidence: 99%
“…Sports-related concussions (SRCs) are common in contact sports such as football, soccer, rugby and ice hockey [ 1 , 2 ]. The incidence has increased in many sports, including ice hockey [ 3 , 4 ]. The majority of SRCs lead to relatively short-lived symptoms, and most athletes return to play (RTP) within a couple of weeks [ 5 , 6 ].…”
mentioning
confidence: 99%
“…In recent decades, SRC has become an growing problem in Swedish ice hockey [ 3 ], and improved treatments are urgently needed. In this study, our aim was to investigate whether early selective head–neck cooling treatment improves outcome in Swedish professional ice hockey players.…”
mentioning
confidence: 99%